Development of a Formulation and In Vitro Evaluation of a Pulmonary Drug Delivery System for a Novel Janus Kinase (JAK) Inhibitor, CPL409116 - Aleksandra Rzewińska; Jakub Szlęk; Damian Dąbrowski; Ewelina Juszczyk; Katarzyna Mróz; Heikki Räikkönen; Mia Siven; Maciej Wieczorek; Przemysław Dorożyński (MDPI AG, 2024)
The pursuit of targeted therapies for cytokine-dependent diseases has led to the discovery of Janus kinase (JAK) inhibitors, a promising class of drugs. Among them, CPL409116, a selective dual JAK and rho-associated protein kinase inhibitor (ROCK), has demonstrated potential for treating conditions such as pulmonary fibrosis exacerbated by the COVID-19 pandemic. This study investigated the feasibility of delivering CPL409116 via inhalation, with the aim of minimizing the systemic adverse effects associated with oral administration. Two micronization methods, jet milling and spray drying, were assessed for CPL409116, with spray drying chosen for its ability to produce an amorphous form of the compound. Moreover, parameters such as the mixing energy, drug load, and force control agent significantly influenced the fine particle fraction (FPF), a critical parameter for pulmonary drug delivery. This study provides insights into optimizing the formulation parameters to enhance the delivery efficiency of CPL409116 to the lungs, offering potential for improved therapeutic outcomes in cytokine-dependent pulmonary diseases.